Implementation of the lalaran method to enhance learning motivation of musthalah hadith among class ix students at madrasah tsanawiyah pondok pesantren al islam darul falah - Ibrahim; Edy Muslimin; Habib Assalam (At Turots: Jurnal Pendidikan Islam, 2024)
This research aims to analyze the implementation of the lalaran method in increasing student learning motivation toward the Musthalah Hadith subject in class IX of Madrasah Tsanawiyah Pondok Pesantren Al Islam Darul Falah. Musthalah Hadith is a subject rich in technical terminology and abstract concepts, requiring a learning approach that can strengthen memorization ability and conceptual understanding. The lalaran method, based on intensive oral repetition, is one of the traditional pesantren (Islamic boarding school) methods that have proven effective in helping students master Islamic texts. The results show that implementing the lalaran method can increase student learning motivation, both intrinsically and extrinsically. Students became more active, and disciplined, and showed improved retention of the material. Additionally, this method strengthens the pesantren learning culture that emphasizes memorization skills and togetherness in the learning process. The implications of these findings provide a foundation for educators and madrasah administrators to adopt contextual learning methods based on pesantren.